Strategic Governance and Financing: Keys to Firm Value in Food and Beverage Companies - Nopitasari Nopitasari (Yayasan Az Zukhruf Cendikia, 2025)
Objective – This study aims to examine the relationship between independent board of commissioners, institutional ownership and capital structure on firm value. Design/methodology/approach – The population in this study is a food and beverage subsector companies listed on the Indonesia Stock Exchange in the period 2013-2022 with a total of 26 companies. The sample selection was carried out using purposive sampling method and obtained a total sample of 13 companies and 130 observations. The analytical technique used to test the hypothesis is multiple regression analysis using IBM SPSS 24 software. Findings – The results of this study indicate that the variable independent board of commissioners and capital structure have a positive and significant effect on firm value, while the variable institutional ownership has no effect on firm value. Originality/value – In this study the focus is on food and beverage subsector companies with a 10 years period from 2013-2022 which can differentiate it from previous research.